Germans in America a concise history - Kamphoefner, Walter D. 1948- (The American ways series, 2021)
From the first arrivals at Germantown, Pennsylvania in 1763 to the twilight of ethnicity in the twenty-first century, this book surveys the sweep of German American history over 300 years. It presents not only the institutions German immigrants created, but also their individual and collective voices as they established their lives within American society.